2017
DOI: 10.2196/resprot.5833
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Combination HIV Prevention for Youth in High-Burden Settings: The MP3 Youth Observational Pilot Study Protocol

Abstract: BackgroundNearly three decades into the epidemic, sub-Saharan Africa (SSA) remains the region most heavily affected by human immunodeficiency virus (HIV), with nearly 70% of the 34 million people living with HIV globally residing in the region. In SSA, female and male youth (15 to 24 years) are at a disproportionately high risk of HIV infection compared to adults. As such, there is a need to target HIV prevention strategies to youth and to tailor them to a gender-specific context. This protocol describes the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Five studies used a pre/post design,36 41–45 and one reported baseline data from a pre/post study 46. Two studies used a cohort study design,47 48 and two used a cross-sectional design with statistical matching 19 49…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies used a pre/post design,36 41–45 and one reported baseline data from a pre/post study 46. Two studies used a cohort study design,47 48 and two used a cross-sectional design with statistical matching 19 49…”
Section: Resultsmentioning
confidence: 99%
“…The included studies described similar biomedical components that included HIV testing and counselling, condom distribution and linkages to other health services. Unique components included PrEP delivered to youths through mobile health events and voluntary medical male circumcision and family planning 47…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations